Self-organization in dipolar cube fluids constrained by competing anisotropies. Issue 7 (26th January 2018) - Rossi, Laura; Donaldson, Joe G.; Meijer, Janne-Mieke; Petukhov, Andrei V.; Kleckner, Dustin; Kantorovich, Sofia S.; Irvine, William T. M.; Philipse, Albert P.; Sacanna, Stefano
Abstract : We disclose the unique magnetic properties of cubic hematite particles and show that their self-assembly behavior is driven by competing anisotropic interactions caused by their shape and fixed dipole moment. Abstract : For magnetite spherical nanoparticles, the orientation of the dipole moment in the crystal does not affect the morphology of either zero field or field induced structures. For non-spherical particles however, an interplay between particle shape and direction of the magnetic moment can give rise to unusual behaviors, in particular when the moment is not aligned along a particle symmetry axis. Here we disclose for the first time the unique magnetic properties of hematite cubic particles and show the exact orientation of the cubes' dipole moment. Using a combination of experiments and computer simulations, we show that dipolar hematite cubes self-organize into dipolar chains with morphologies remarkably different from those of spheres, and demonstrate that the emergence of these structures is driven by competing anisotropic interactions caused by the particles' shape anisotropy and their fixed dipole moment. Furthermore, we have analytically identified a specific interplay between energy, and entropy at the microscopic level and found that an unorthodox entropic contribution mediates the organization of particles into the kinked nature of the dipolar chains.